Мифо-архетипические мотивы психобиографии Тараса Шевченко - Betko, Iryna (Acta Neophilologica, 2021)
The study of various aspects of the symbolic biography of Taras Shevchenko is a contemporary direction of modern Ukrainian literary criticism. This article analyzes the mythological and archetypal motifs in Great Mother. They played a special role in the life and work of the poet, who never made up for the slave and orphan complexes. The strategy of symbolic-biographical analysis significantly expands the psychoanalytic context of the study.